Resenha: Disseminação da ciência via acesso aberto - Blattmann, Ursula (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2011)
Resenha do livro: CANESSA, Enrique; ZENNARO, Marco. Science Dissemination using Open Access: A compendium of selected literature on Open Access. ICTP - The Abdus Salam International Centre for Theoretical Physics 2008. 207p. ISBN 92-95003-40-3. link para o texto completo: http://revista.acbsc.org.br/index.php/racb/article/view/670/736